Generation Z’s Purchasing Intention of Cruelty-free Cosmetic Products: The Moderating Role of Environmental and Animal Welfare Concerns - Bonifacio, Ralph Allen; Baui, Alyssa Faye; Uy, Maria Yza Thalia; Bandojo, Agnes Jocelyn; Etrata, Antonio (International Business Education Journal, 2024)
Numerous brands worldwide offer cruelty-free products due to consumers' increasing support against the unethical practice of animal testing and the demand for sustainability in the cosmetics industry. However, there was a considerable gap between the use of environmental and animal welfare concerns as the moderating variable to attitudes, social influence, and awareness of consumers to issues and their effect on the purchasing intention of cruelty-free cosmetic products. This paper determined if environmental and animal welfare concerns moderated the factors affecting Generation Z's purchasing intention of cruelty-free cosmetic products. The study used a descriptive-correlational research design and purposive sampling method. Google Form survey questionnaires were distributed and answered by 220 respondents aged 18 to 26 living in the National Capital Region. Furthermore, Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to examine the hypotheses. The findings emphasized that environmental and animal welfare concerns moderated the effect of attitude, consumer awareness, and social influence on the purchasing intention of cruelty-free cosmetic products.  The study concluded that Generation Z prioritized brands committed to ethical production and environmental impact over other factors affecting the purchasing intention of cruelty-free cosmetics, advocating a reconsideration of animal testing practices. This environmental consciousness allowed brands to align with shifting consumer preferences, with practical implications for enhancing market appeal and brand loyalty. Moreover, lawmakers could leverage study insights to refine regulations, promoting ethical practices in the Philippine cosmetic industry.